THE CORRELATION OF AGE AND VISCERAL FAT WITH TOTAL CHOLESTEROL - Yuliasih; Nurdin, Fatah; Tangkudung, Albert Wolter Aridan; Chandra (UNIVERSITAS NEGERI JAKARTA POSTGRADUATE OF PHYSICAL EDUCATION DEPARTMENTS, 2024)
This study aims to determine the correlation between age, and visceral fat with total cholesterol. The method used is a cross-sectional approach. For the population of RPTRA visitors in East Jakarta, the sampling technique with accidental sampling is based on chance. The result of this study is that age (X1) to total cholesterol (Y) correlates to 0.290. While visceral fat (X2) to total cholesterol (Y) correlates to 0.432, there is a moderate correlation between visceral fat and total cholesterol. So, age does not affect total cholesterol or visceral fat. Some of the factors that affect the increase in cholesterol are diet and activity.